Developing the latest framework to measure and incentivise pharmaceutical industry contributions to health research and development - Clarke B. Cole; Stine Trolle; Danny J. Edwards (BMC, 2018)
Abstract Major pharmaceutical companies contribute important expertise to health research and development (R&D), particularly in their ability to develop and bring pharmaceuticals to market. The Access to Medicine Index evaluates how 20 of the world's largest pharmaceutical companies are directing R&D efforts towards the needs of people living in low- and middle-income countries. In dissemination of its findings, the Index stimulates pharmaceutical companies to expand R&D activities in this direction. The Index methodology is reviewed every 2 years, most recently for the 2018 Index, to ensure their R&D activity is benchmarked against current health R&D priorities as defined by the global health community. The review is based on consensus-building processes involving global health stakeholders. In the latest review, two main changes to the methodology were made that will further deepen the Index's analysis of (1) how far companies' R&D activity aligns with global health priorities; and (2) whether companies make plans to ensure resulting innovations reach populations in need globally. These changes will be applied in the 2018 Access to Medicine Index. Importantly, the methodology review process highlighted the need for further prioritisation from the global health community, in particular to emphasise to innovators which product innovations are needed most critically to address the burden of non-communicable diseases in low- and middle-income countries. Should such prioritisations be developed, the Index can play an important role in tracking and stimulating company contributions towards them.